Analisis Yuridis terhadap Putusan Pengadilan Negeri Kupang Nomor 81/PID.SUS-TPK/2022/PN KPG Terkait Tindak Pidana Korupsi dalam Penjualan Tanah Waris Tanpa Sertifikat kepada Pemerintah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the considerations of the judge in the decision of the Kupang District Court No. 81/Pid.Sus-TPK/2022/PN Kpg and the legal implications of the application of Article 3 of the Corruption Eradication Law. This research uses a normative legal method with a statutory and conceptual approach. The results show that the application of Article 3 of the Corruption Eradication Law in this case is incorrect, as the defendant is not a public official and does not have authority over the management of state finances or assets. It was also found that there was a misapplication of the law (error in juris), an error in determining the subject of the law (error in persona), and an inaccuracy in the object of the case (error in objecto). This study concludes that the case is more appropriately classified as an administrative error by state apparatus rather than a corruption crime. Academically, this research reinforces the distinction between administrative law and criminal law regarding corruption. Socially, this research emphasizes the importance of legal certainty protection and the prevention of criminalization of civil society. This study provides an important contribution to the development of legal theory, as well as the protection of individual rights in the context of criminal law.